Kolaborasi Kelompok Usaha Bersama (KUB) “Perempuan Rengganis” dalam Meningkatkan Kesejahteraan Ekonomi Desa Klungkung - Husniah, Furoidatul; Umniyyah, Zahratul; Taufiq, Akhmad; Dwi Eriyanti, Linda; Makmur, M. Hadi; Rohman, Hermanto; Prasetyowati, Irma (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2024)
This study uses a qualitative descriptive method with a case study approach. Data were obtained through direct observation and in-depth interviews with the administrators and members of KWT, RDS, and village officials. The results of the study indicate that the formation of the Joint Business Group (KUB)